IMPLEMENTASI PERATURAN BUPATI NOMOR 84 TAHUN 2018 TENTANG ALOKASI DANA DESA DALAM UPAYA PENINGKATAN KEGIATAN PEMBANGUNAN INFRASTRUKTUR DI KECAMATAN SAMBI KABUPATEN BOYOLALI - Dhiyan Kartika Dewi (JI@P, 2021)
The village government as the lowest layer of government directly facing thecommunity is required to hold an effective government and plan developmentwell.The obstacle faced by the village government in Sambi sub-district is the roleof the community in infrastructure development, the village government is lessexpert at compiling village documents.The method used in this study is descriptivequalitative by using the theory of policy implementation put forward by GoergeEdward III where variables that determine the effectiveness of implementation arecommunication, resources, disposition and bureaucratic structure.Theimplementation of village funds in infrastructure development in Sambi Subdistrict, on communication indicators has been good, where the village governmentheld a village development before village funds were implemented to buildinfrastructure. People give opinions in the musrenbangdes.Indicators of villagedevice resources in the village government need to receive guidance and directionin implementing this village fund.Human resources in the community are adequatebecause many people already have the title of S-1.Indicators of disposition includecommitment, nature of democracy, honesty, attitude of implementors have beenvery good in implementing village funds according to Perbup No. 84 of 2018 bycarrying out development and accountable administratively.IndikaktorBureaucratic structure in the formation of bureaucratic structure of village fundimplementation has not been in accordance with the toxic.Keywords: Implementation, Village Fund, Infrastructure